Corporate Criminal Liability For Environmental Crimes in Indonesia: A Normative Legal Analysis - Marbun, Christian Dody Diori (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Corporate involvement in environmental crimes has emerged as an increasingly complex legal challenge in Indonesia, given its profound consequences for ecological sustainability and public welfare. This study examines the normative construction of corporate criminal liability within Indonesia's positive legal framework and identifies juridical obstacles undermining enforcement effectiveness. A normative legal research method was employed, incorporating statute, conceptual, and comparative approaches. Although legal instruments such as Law No. 32 of 2009, Supreme Court Regulation No. 13 of 2016, and Law No. 1 of 2023 provide a formal basis for corporate criminal accountability, their implementation is hindered by normative inconsistencies. Key obstacles include difficulties in proving corporate mens rea, limited institutional capacity, regulatory ambiguity, and absence of Piercing the Corporate Veil integration. These conditions create normative gaps perpetuating weak corporate accountability recurring environmental violations. This study recommends regulatory reformulation, harmonization of legal instruments, strengthened institutional capacity toward effective and equitable environmental justice.